Valuing scenic amenity using life satisfaction data - Ambrey, C; Fleming, C. M. (Griffith University, 2011)
The life satisfaction approach has recently emerged as a new technique in the suite of options available to non-market valuation practitioners. Employing data from the Household, Income and Labour Dynamics in Australia (HILDA) survey and Geographic Information Systems (GIS), this paper examines the influence of scenic amenity on the life satisfaction of residents of South East Queensland (SEQ), Australia. Measuring scenic amenity on a 10-point scale, it is found that, on average, a respondent is willing to pay approximately AUD$12,000 in household income per annum to obtain a one-unit improvement in scenic amenity. However, on closer inspection, we find that the relationship between willingness-to-pay and the level of scenic amenity is not linear. To our knowledge, this is the first paper to value scenic amenity using the life satisfaction approach and is the first paper to use this approach to value any type of environmental good or service in SEQ. As such, this paper represents a genuine contribution to a small, yet growing, body of literature.
Discussion Papers Economics
Economics Working Papers
Keywords: Satisfaction -- Life; Lifestyle; Satisfaction; Life; Lifestyle